Pengaruh Metode Pelatihan Terhadap Kompetensi Karyawan NDT (Non Destructive Test) pada PT XYZ - Vikry Setiawan; Rahmat Hidayat (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This study aims to determine the effect of the implementation of the training methods of the competence of employees in the NDT (Non Destructive Test). NDT is a department that plays a role in the trial of goods without damaging the item or object. Implementation of training methods is divided into two methods: On the Job Training & Off The Job Training. This method is expected to improve the competence of employees. Respondents of this research is the employee who worked on the NDT (Non Destructive Test), the results showed that there was a significant effect of variable On The Job Training for the competence of employees is 0.650, and there is a positive and significant influence of variables Off The Job Training for employee competence of 0.628 on the NDT (Non Destructive Test) at XYZ